2021
DOI: 10.1007/s00392-020-01801-y
|View full text |Cite
|
Sign up to set email alerts
|

Impaired in vitro growth response of plasma-treated cardiomyocytes predicts poor outcome in patients with transthyretin amyloidosis

Abstract: Objectives Direct toxic effects of transthyretin amyloid in patient plasma upon cardiomyocytes are discussed. However, no data regarding the relevance of this putative effect for clinical outcome are available. In this monocentric prospective study, we analyzed cellular hypertrophy after phenylephrine stimulation in vitro in the presence of patient plasma and correlated the cellular growth response with phenotype and prognosis. Methods and results Progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Furthermore, Hein et al demonstrated that the plasma of healthy individuals or patients with hereditary transthyretin amyloidosis with polyneuropathy promotes hypertrophy of neonatal rat cardiomyocytes induced by phenylephrine, while the plasma of patients with hereditary transthyretin cardiac amyloidosis or wild-type ATTR cardiac amyloidosis attenuated the hypertrophic response in vitro. They also reported that an attenuated cardiomyocyte hypertrophic response after stimulation with patients’ plasma in vitro is an independent risk factor for adverse cardiac events (death, transplantation and/or cardiac decompensation) in ATTR patients [ 69 ].…”
Section: Molecular Mechanisms Of Amyloidosismentioning
confidence: 99%
“…Furthermore, Hein et al demonstrated that the plasma of healthy individuals or patients with hereditary transthyretin amyloidosis with polyneuropathy promotes hypertrophy of neonatal rat cardiomyocytes induced by phenylephrine, while the plasma of patients with hereditary transthyretin cardiac amyloidosis or wild-type ATTR cardiac amyloidosis attenuated the hypertrophic response in vitro. They also reported that an attenuated cardiomyocyte hypertrophic response after stimulation with patients’ plasma in vitro is an independent risk factor for adverse cardiac events (death, transplantation and/or cardiac decompensation) in ATTR patients [ 69 ].…”
Section: Molecular Mechanisms Of Amyloidosismentioning
confidence: 99%
“…In vitro, it has been demonstrated that isolated cardiomyocytes, when cultured with various TTR species in the culture media, exhibit cytotoxicity with increased ROS production and altered calcium transient and action potential repolarization profiles (Sartiani et al, 2016). Additionally, human‐induced pluripotent stem cell‐derived cardiomyocytes (iPSC‐CM) cultured with plasma from wtATTR exhibit impaired growth responses compared to iPSC‐CM cultured with plasma from healthy patients (Hein, Furkel, et al, 2021). Here, the focus is to understand how underlying TTR fibrils affect cardiomyocytes cultured on different engineered substrata in order to best recapitulate cardiomyocyte biology in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Morphological readout in cardiovascular research is still limited to cell size and a few selected features (e.g., perimeter, elongation, and form factor). 9,10 Alternative methods focus on sarcomere organization, 3D volume/ shape, proliferation, or reporter readouts. [11][12][13][14] However, these established methods address only specific parts of morphology, and integrated approaches are not established for use in cardiovascular research.…”
Section: Introductionmentioning
confidence: 99%